2011
DOI: 10.1016/j.jpainsymman.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Tensions: Integrating Palliative Care Consultation Services Into an Academic Medical Center Setting

Abstract: Context Despite rapid proliferation of hospital-based palliative care consultation services (PCCS) across the country, there is little description of the dynamic processes that the PCCS and the non-PCCS hospital cultures experience during the institutionalization of a successful PCCS. Objectives To describe the institutionalization of a new PCCS in a quaternary care academic medical center (AMC) and highlight two themes, cost and quality, that pervaded the dynamics involved from the inception to the successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Information regarding the challenges of clinical growth [1618] and staffing allocation [1921] of palliative care programs is limited. Here we describe the growth and staffing structure of an integrated palliative care program comprising an inpatient PCU, a mobile consult service, and an outpatient supportive care clinic at a comprehensive cancer center over a 10-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Information regarding the challenges of clinical growth [1618] and staffing allocation [1921] of palliative care programs is limited. Here we describe the growth and staffing structure of an integrated palliative care program comprising an inpatient PCU, a mobile consult service, and an outpatient supportive care clinic at a comprehensive cancer center over a 10-year period.…”
Section: Introductionmentioning
confidence: 99%
“…15 This anxiety may make them uncomfortable or unwilling to broach the idea of a palliative care consultation with a patient or a patient's family. 11 Aslakson et al 13 found that when surgeons attempted to open discussions about palliative care with patients, the discussions were often quick, inadequate, and ineffective. A variety of strategies have been suggested to overcome the reluctance of health care providers to initiate discussions about palliative care.…”
Section: Difficulty Initiating a Palliative Care Discussion As A Barrmentioning
confidence: 99%
“…11 Some physicians think that introducing palliative care means that they must "give up" trying to cure their patients, something that they are unwilling to do because their patients might die sooner. physicians that they alone should provide total care to their patients, 5,13 that they already provide good palliative care themselves, 11 and a lack of knowledge among many health care providers about the extent and variety of palliative care services available at their institutions. 13 These barriers can be overcome with education about and experience with palliative care.…”
Section: Misunderstandings As a Barrier To Palliative Care Consultationmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Challenges or 'barriers' to delivering palliative care in hospital persist, including delays in recognising the need for palliative care and in referral for specialist advice. 21,22 In cancer centres there are additional challenges to referrals: 23 it may be perceived as an end to cancer treatment, synonymous with a loss of hope for the patients as well as a concern that they will feel abandoned by oncology services. Only through rigorous evaluation of outcomes and joint research will evidence be provided to support the continuation of palliative care in an era of figure 1 Conception of an Acute Palliative Care Unit.…”
Section: Recognising the Problemmentioning
confidence: 99%